Impact of breast cancer neoadjuvant chemotherapy on plasma and urine amino acid profile, plasma proteins and nitrogen metabolism - Dastych, Milan; Holánek, Miloš; Gottwaldová, Jana; Čermáková, Zdenka; Mikušková, Alena (Scandinavian journal of clinical and laboratory investigation, 2024)
Neoadjuvant chemotherapy (NAC) is the preferred treatment option in locally advanced breast cancer (BC). The administration of NAC is associated with a wide range of adverse effects. This pilot observational prospective study examined the effect of NAC using anthracycline + cyclophosphamide (AC) followed by paclitaxel (PTx) on a portfolio of 22 plasma and urinary amino acids, plasma proteins (albumin, prealbumin, transferrin), and products of nitrogen metabolism (urea, creatinine, uric acid) in plasma and urine. Plasma and 24-h urine samples were obtained from ten patients with early breast cancer (N1-3 N0-2 M0), at the following time points: before the start of NAC and during the AC/PTx treatment period (a total of 8 measurements at three-weekly intervals). Amino acids were analyzed using ion exchange chromatography. There were no significant differences in the measured parameters in plasma and urine between pre-NAC and during AC- and PTx-treatment. No trend was detected. A significant difference in the portfolio of plasma and urinary amino acids was found only in the pre-treatment period compared to the control group. Levels of eight plasma amino acids (8/22) were significantly reduced and those of nine urine amino acids were increased (9/22). Nitrogenous catabolites in plasma and urine were not indicative of increased protein catabolism during the anthracycline and taxane treatment periods. A slightly positive nitrogen balance was accompanied by an average weight gain of 3.3 kg (range 0-6 kg). The AC/PTx treatment regimen did not cause significant changes in the monitored laboratory parameters.
Keywords: amino acids; Anthracyclines; neoadjuvantní terapie; breast cancer; Humans; Nitrogen; dusík; lidé středního věku; kreatinin; nitrogen metabolism; Female; Aged; dospělí; protokoly protinádorové kombinované chemoterapie; krevní proteiny; plasma proteins; senioři; lidé; Creatinine; aminokyseliny; pilotní projekty; Amino Acids; Pilot Projects; antracykliny; Blood Proteins; Adult; Breast Neoplasms; ženské pohlaví; Middle Aged; paclitaxel; Antineoplastic Combined Chemotherapy Protocols; Cyclophosphamide; Neoadjuvant Therapy; nádory prsu; Paclitaxel; prospektivní studie; Neoadjuvant chemotherapy; cyklofosfamid; Prospective Studies